Characterization of the vestibular function in an otosclerosis population – a pilot case-control study - Miguel Campos Lopes; Alexandra Correia; Hélder Silva; Natália Oliveira; Diana Ribeiro; Vanessa Neves; Vera Miranda; Carlos Carvalho (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Objectives: Characterization of the vestibular function in an otosclerosis population, and its comparison with a healthy population.